Archaeological site archive – development of archaeological field documentation - Jezeršek, Mirjam (Atlanti +, 2025)
Purpose: The archaeological site archive consists of archaeological finds, sam-ples, and all documentation accompanying archaeological research and exca-vation or post-excavation processing. This documentation must be permanently stored as a collection in the relevant museum institution. Part of the documen-tation is also the archaeological field documentation, which is the subject of this research. The purpose of this article is to provide a systematic overview of the development and current state of archaeological field documentation and to identify current issues. What was the development of archaeological field docu-mentation and what types of documents did it contain, and does it contain?Methodology: The research uses a compilation/description method based on already established research and publications in this field.Findings: A review of literature has shown that Slovenian archaeologists only began to deal with archaeological field documentation in the late 1950s. Since the 1980s, the scope of fieldwork has increased significantly, and initiatives for the standardization of archaeological field documentation have begun to emerge. In 2013, the Rules on Archaeological Research were adopted, part of which is Annex 1: Professional Standards for Archaeological Field Research, which sets stand-ards for archaeological field documentation. Archaeologists have been aware and are still conscious of the problem of non-standardization of archaeological field documentation, which is also evident in its archiving.Conclusion: The standardization of archaeological field documentation is quite vague and does not contain precise and clear instructions, so the field remains rather undefined. Its status within the archive of an archaeological site in a mu-seum remains unclear
Keywords: archaeological field documentation; archaeological site archive; arheološka terenska dokumentacija; arheološki arhiv; development; razvoj; regulation; Slovenian archaeology; slovenska arheologija; ureditev